Two-photon calcium imaging of seizures in awake, head-fixed mice. (June 2021) - Somarowthu, Ala; Goff, Kevin M.; Goldberg, Ethan M.
Graphical abstract: Highlights: Two-photon calcium imaging can be used to study mechanisms of seizures in awake, head-fixed mice. This includes a mouse model of Dravet syndrome ( Scn1a +/− mice). Cerebral cortex GABAergic interneurons are differentially recruited during seizures. Abstract: Epilepsy is a severe neurological disorder defined by spontaneous seizures. Current treatment options fail in a large proportion of patients, while questions as to the basic mechanisms of seizure initiation and propagation remain. Advances in imaging of seizures in experimental model systems could lead to a better understanding of mechanisms of seizures and epilepsy. Recent studies have used two-photon calcium imaging (2 P imaging) in awake, behaving mice in head-fixed preparations to image seizures in vivo at high speed and cellular-level resolution to identify key seizure-related cell classes. Here, we discuss such advances and present 2 P imaging data of excitatory neurons and defined subsets of cerebral cortex GABAergic inhibitory interneurons during naturalistic seizures in a mouse model of Dravet syndrome ( Scn1a +/- mice) along with other behavioral measures. Results demonstrate differential recruitment of discrete interneuron subclasses, which could inform mechanisms of seizure generation and propagation in Dravet syndrome and other epilepsies.